Plan De Negocios Para La Apertura De Una Microempresa “Rodamientos Y Bolineras Nel” Ubicada En Bogotá (2021)
The main objective of this project is to determine the viability of the sale of goods from specialized bearing autoparts such as Chevrolet, Renault and Mazda in the automotive sector. The business where it would be located is in the city of Bogota in the sector of Bosa the station, having as much competition, but it is also where the potential market is located, as it is where consumers come when they need a product for their vehicle. This business plan is made using the canvas model allowing to know and evaluate the relationship between customers, suppliers, costs and products.